UJI EFEK ANTIINFLAMASI EKSTRAK ETANOL KULIT BUAH MAHKOTA DEWA (PHALERIA MACROCARPA BOERL.) TERHADAP EDEMA KAKI TIKUS PUTIH JANTAN - Dawud, Firman (PHARMACON, 2014)
This study to prove the ethanol extract of the Mahkota Dewa skin fruit has antiinflammatory effects on foot edema white male rats by induced 5 % solution of white egg and determine ethanol extract dose from Mahkota Dewa Skin Fruit that most effective for decrease the volume of foot edema white male rats induced 5 % solution of white egg . This study used 15 white male rats and divided into 5 groups, negative control group (aquadest), positive control group (natrium diclofenac), treatment group (ethanol extract of Mahkota Dewa Skin Fruit dose 140mg/200gBB , 280mg/200gBB , 420mg/200gBB . after oral gived, the rat foot edema made by  induced of a 5% solution of white egg . Rat foot Volumes measured every 1 hour for 7 hours . Based on the results of the study , the ethanol extract of Mahkota Dewa Skin Fruit with a dose 140mg/200gBB have antiinflammatory Effects 16,91 %, 280mg/200gBB by 18.87 % and 420mg/200gBB by 19.09 % and the most effective dose to decrease the volume of foot edema white male rats from ethanol extract of Mahkota Dewa Skin Fruit at doses 420mg/200gBB that have antiinflammatory Effects 19,09 %.   Key words : Antiinflammatory, edema, Phaleria macrocarpa Boerl